Creating Serious Robots That Improve Society - Imberman, Susan; McManus, Jean; Otts, Gina (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
The Grace Hopper conference has many lectures/activities for participants. Tech Node presentations at this conference are two hours and focus on encouraging open discussion around a topic. This "not so grand" challenge, originally created for this conference, requires participants to brainstorm a robot creation that could somehow improve society in one of four societal areas: Elder Care (non- medical), Search and Rescue, Environment, and Affordable Home Health Care. This project format also can be used as an unplugged activity for a CS0/CS1 class or as a more advanced project that employs image processing and AI techniques such as machine learning.